Pelatihan Layanan Bimbingan Kelompok Dengan Menggunakan Teknik Token Economy Untuk Meningkatkan Minat Belajar Siswa Kelas X Di MAN Kota Palangka Raya - Mimi Suratie; Oktamia Karuniaty Sangalang; May Cynthia Sitompul (Jurnal Pengabdi, 2022)
nterest is an impulse from within a person to do something with pleasure or pleasure without coercion from other parties. However, many students still have low interest in learning. This study was conducted to determine whether the application of group guidance services using the token economy technique can increase student interest in learning. This research is an experimental research, with a one group pre-test and post-test design. The sample was taken using a non-probability sampling technique so that there were eight students of class X MIPA-4 MAN Palangka Raya City were assigned as samples in this study. Data collection techniques in this study used by researchers are questionnaires, observation, and documentation. Then the researcher analyzed the data using parametric statistics from the Paired Samples Test (SPSS version 22 program) because the researcher's data were normally distributed. The author finally draws conclusions based on statistical results. The results showed that the calculation of the value of the paired t-test obtained was sig.2 tailed of 0.000 <0.05 with a t count of -7.072 which means the null hypothesis is rejected and the alternative hypothesis is accepted. The alternative hypothesis in this study is that the application of group guidance services using the token economy technique can increase student interest in learning for class X MIPA-4 MAN Palangka Raya City. Thus, it can be concluded that the application of group guidance services using the token economy technique can increase student interest in learning for class X MIPA-4 MAN Palangka Raya City for the 2020/2021 academic year.